Modelos de crescimento de jabuticabeiras em distintas condições de ambiente - Porto, Alexandre Hack (2022)
Among the native fruit trees of regional importance in southern Brazil, the jaboticaba tree stands out. However, in the production of jabuticabas, extractivism or the cultivation of isolated plants in backyards prevails, and there are still few commercial orchards. This is due to the lack of genotypes selected as commercial varieties and information on management techniques and associated with the understanding of plant physiology. As the plant originates in an environment with lower luminosity (forests) it is important to understand its growth behaviour under different shading conditions, in order to recommend the best environment for its commercial cultivation in an orchard. This could be done with the hybrid jaboticaba tree, since it offers the best characteristics for its commercial cultivation (early, presence of more than one productive flow per year and tree with less vigour). However, in backyards, the jaboticaba tree is cultivated in full sun, which demonstrates adaptive capacity, it being able to test and monitor the growth of promising genotypes whose matrices are in the forests of the Southwest region of Paraná. The study aimed to estimate, through nonlinear regression models, the growth of hybrid jaboticaba tree genotypes at different light intensities that were evaluated from 2014 to 2021 (experiment 1) and of native jaboticaba tree in orchard conditions where the evaluations comprised the period from 2012 to 2021 (experiment 2). For this, monthly, the stem diameter growth, total plant height, stem height and bud length were evaluated. The growth in volume, biomass and carbon accumulation were measured from the estimates of these evaluations and with data obtained by destructive analysis of sample plants (direct method) to determine wood density, dry mass content and biomass expansion factor. The data adjusted through six non-linear regression models, with the choice of models that best adhered to the data set of each variable, by means of calculations of relative curvatures, analysis of variance, test of comparison of multiple means and test of paired means, on each of the parameters obtained in the selected models, using the computational tool R. The jaboticaba tree evaluated in the two experiments, obtained the best fits with the logistic models of three and four parameters and, the model of Weibull, in which they represented the growth of the variables evaluated. In experiment 1, the management of the simulated light intensity condition with the use of a 50% shading resulted in greater growth when compared to the others. The use of 80% shading in all directions exceeded the limit of adaptive plasticity, harming the growth of hybrid jabuticaba trees. For experiment 2, the places of origin named as Xavier and José, showed better adaptation in the place and in the orchard condition. However, Xavier, Sabará, Marcolina, José, F. Jaboticabal provided higher C in the conditions evaluated. Studies and evaluations of determination of biomass and carbon by the direct method are recommended, for the composition of a database for future interests, not only of jabuticaba trees, but of other species of native fruit trees and species of interest for the composition of agroforestry systems, because these growth, biomass and carbon sequestration studies measure the efficiency of agroforestry systems.